2021
DOI: 10.21203/rs.3.rs-963978/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition from sub-Rayleigh anticrack to supershear crack propagation in snow avalanches

Abstract: Snow slab avalanches are released following anticrack propagation in highly porous weak snow layers buried below cohesive slabs. The volumetric collapse of the weak layer leads to the closure of crack faces followed by the onset of frictional contact. Here on the basis of snow fracture experiments, full-scale avalanche measurements, and numerical simulations, we report the existence of a transition from sub-Rayleigh anticrack to supershear crack propagation involving the Burridge-Andrews mechanism. Remarkably,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Lastly, Trottet et al (2022) very recently showed rupture propagation at supershear speed for snow avalanches, another case exposing low shear wave speeds of the sliding mass (< 120 m s −1 ). We confirm through direct experimental observation of the wavefield generation that unique force mechanisms are relevant for describing slip events between two materials with strong wave velocity contrasts.…”
Section: Relevance For Natural Rupture Processesmentioning
confidence: 99%
“…Lastly, Trottet et al (2022) very recently showed rupture propagation at supershear speed for snow avalanches, another case exposing low shear wave speeds of the sliding mass (< 120 m s −1 ). We confirm through direct experimental observation of the wavefield generation that unique force mechanisms are relevant for describing slip events between two materials with strong wave velocity contrasts.…”
Section: Relevance For Natural Rupture Processesmentioning
confidence: 99%
“…Lastly, Trottet et al. (2022) very recently showed rupture propagation at supershear speed for snow avalanches, another case exposing low shear wave speeds of the sliding mass (<120 m s −1 ) and high material contrasts (0.5–2 vs. 5–30 MPa Young's modulus). Our direct experimental observation of the wavefield generation confirms, that unique force mechanisms are relevant for describing slip events between materials with strong wave velocity contrasts.…”
Section: Relevance For Natural Rupture Processesmentioning
confidence: 99%
“…Geophysical mass flows are common phenomena in mountain regions worldwide, with the size, frequency, and hazardous potential of events predicted to increase due to extreme rainstorms, land‐cover changes, and severe wildfires (Hoch et al., 2021; D. Li et al., 2022; Pisano et al., 2017). Compared with traditional rigid countermeasures (Hungr et al., 1984), flexible barriers are increasingly used to mitigate catastrophic geophysical flows (Figure S1 in Supporting Information S1), such as debris flows, debris/rock/snow avalanches, and rockfalls (Caviezel et al., 2021; Cook et al., 2021; Iverson et al., 2011; Trottet et al., 2022). A fundamental issue in hazard mitigation is determining the total impact load of geophysical flows on a flexible barrier.…”
Section: Introductionmentioning
confidence: 99%